Estudios epidemiológicos del alfalfa enamovirus-1 en el cultivo de alfalfa de Argentina - Trucco, Veronica Milagros; Cabrera Mederos, Dariel; Castellanos Collazo, Onias; Vaghi Medina, Carlos Gaston; Lenardon, Sergio Luis; Giolitti, Fabian (Asociación Argentina de Fitopatólogos, 2021)
Poster